Comparison of Capitalist and Socialist Economic Models in International Trade - Salimah, Nur; Siallagan, Maya Adelina; Banjarnahor, Heru Elpando; Matondang, Khairani (Journal of Business Management and Economic Development, 2023)
This study discusses the comparison between capitalist and socialist economic models in the context of international trade. A qualitative approach is used by analyzing references from several books and journals related to this topic. The research results show that in the capitalist economic model, international trade is used as a means to increase profits and economic growth, by prioritizing the interests of individuals and private companies. On the other hand, in the social economic model, international trade is seen more as a tool to meet people's needs and increase the distribution of wealth, with the pressure of collective ownership and the government as regulator. Although both have their advantages and disadvantages, this research shows that in the context of international trade, the social economic model has more potential to create more equitable distribution and social justice the original work.